Improvement of Seeds Germination of Carob Trees (Ceratonia Siliqua L.) by Using Different Treating Methods - Salih , Sami Mohammed; Abdulrraziq, Ahmed Amrajaa (Al-Mukhtar Journal of Sciences, 2018)
This study was conducted at the Faculty of Science / Omar Al-Mukhtar University to improved the tree seeds germination of Carob (Ceratonia siliqua L.) wild and cultivated by using a number of different treatments, inclued the treatment of soaking in hot water for periods (20, 40 and 60) minute, scarified mechanical, scarified mechanical with soaking in distilled water, and scarified mechanical soaking in gibberellin 500ppm, without scarifying and with soaking in gibberellin concentrations 750, 1000, and 1250pmm, and with soaking in concentrations 50, 70, and 90% Of sulphruic acid. The treatment of scarifying with soaking in gibberellin 500ppm was moer efficiency than all treatments with germination percentage (98%), germination time (2.88 day), and the best averages of germination index, as root length, fresh weight, and dry weight of the seedling. While the lowest germination percentage and longest germination time was was recorded treatment of soaking in different concentrations of gibberellin. The results showed no significant differences between wild and planted Ceratonia siliqua L. seeds for studied traits. The study concluded that the treatment of Ceratonia siliqua L.seeds by scarifying with soaking in gibberellin 500ppm was the most efficient in improving germination.